2011
DOI: 10.1089/ten.tea.2010.0459
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoid Cells on Culture Plates and Collagen Scaffolds: Phenotype and Transport Properties

Abstract: Cells isolated from the anterior brain stem exhibited the same phenotype as those found in the native tissue and exhibited aspects of barrier function found in vivo. These studies suggest that an ex vivo model for the arachnoid granulation can be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Arachnoidal tissue exists in multiple forms including membranes, dense granulation caps, and porous central cores (Kida et al, 1988). The degree of intracellular or extracellular matrix pathway involvement in transport is probably dependent on this local structure of the arachnoid tissue, but preliminary tracer studies have shown that permeabilities of low molecular weight substances in confluent monolayers parallel that of the BBB (Holman et al, 2010;Lam et al, 2011). Tight junctions crucial to the integrity of the BCB and regulation of paracellular transport have also been seen in the arachnoid cell-cell contacts with transmission electron microscopy (Hasegawa et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Arachnoidal tissue exists in multiple forms including membranes, dense granulation caps, and porous central cores (Kida et al, 1988). The degree of intracellular or extracellular matrix pathway involvement in transport is probably dependent on this local structure of the arachnoid tissue, but preliminary tracer studies have shown that permeabilities of low molecular weight substances in confluent monolayers parallel that of the BBB (Holman et al, 2010;Lam et al, 2011). Tight junctions crucial to the integrity of the BCB and regulation of paracellular transport have also been seen in the arachnoid cell-cell contacts with transmission electron microscopy (Hasegawa et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Because CSF bathes the arachnoid providing 5mTHF for its further development, abundant available 5mTHF in CSF may lead to overstimulation of arachnoid cell division that results in changes in tridimensional structure, and somehow, in a dysfunctional arachnoid tissue that is unable to perform its remarkable function of transporting CSF across the CBB and thus maintaining CSF flow and pressure homeostasis. 46,54,55 These events may contribute to CSF obstruction and consequently may lead to congenital HC as has been reported previously. 56 It is interesting to speculate that CSF folate imbalance may also be responsible for arachnoid granulations observed in ageing human brains considering the correlation of decreased CSF volume production, perhaps indicating drainage insufficiency, associated with dementia for example.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, we propose that the primary tumor may be releasing "unhinged" arachnoid cap cells, which were found in case 1's pathology. Arachnoid cap cells are highly secretory, [17][18][19] and we posit that these microdeposits may have the ability for aberrant secretion of fluid to form these cystic lesions. We do, however, acknowledge that longer-term follow-up is necessary to truly define the natural history of these seemingly benign lesions.…”
Section: Discussionmentioning
confidence: 94%